(untitled) - Richards, Jack C. (Oxford, 2012)
Comprehensively revised and expanded to provide more listening input and a new focus on developing test-taking skills
Nghe - Nói C1.1,Nghe - Nói B2.2
Keywords: English language,English language,Tiếng Anh; Textbooks,Textbooks for foreign speakers,Giáo trình